2019
DOI: 10.1152/ajpheart.00780.2018
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin receptor knockdown in the paraventricular nucleus of the hypothalamus attenuates hypertension development and AT1 receptor-mediated calcium events

Abstract: Activation of the brain renin-angiotensin system (RAS) is a pivotal step in the pathogenesis of hypertension. The paraventricular nucleus (PVN) of the hypothalamus is a critical part of the angiotensinergic sympatho-excitatory neuronal network involved in neural control of blood pressure and hypertension. However, the importance of the PVN (pro)renin receptor (PVN-PRR)—a key component of the brain RAS—in hypertension development has not been examined. In this study, we investigated the involvement and mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 93 publications
4
37
0
Order By: Relevance
“…In addition, we found that the PRR in the PVN and RVLM is predominantly expressed in neurons, and not astrocytes, a finding in accord with those of our previous study on the human SFO (Cooper et al, 2018). In vivo studies in rodents have similarly found that the PRR is expressed in neurons but not in astrocytes (Shan et al, 2008;Huber et al, 2015;Souza et al, 2019). This cell-type expression pattern extends to in vitro cell culture studies, which have also shown that the PRR is expressed in neurons but not astrocytes (Shan et al, 2010;Peng et al, 2013;Shi et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In addition, we found that the PRR in the PVN and RVLM is predominantly expressed in neurons, and not astrocytes, a finding in accord with those of our previous study on the human SFO (Cooper et al, 2018). In vivo studies in rodents have similarly found that the PRR is expressed in neurons but not in astrocytes (Shan et al, 2008;Huber et al, 2015;Souza et al, 2019). This cell-type expression pattern extends to in vitro cell culture studies, which have also shown that the PRR is expressed in neurons but not astrocytes (Shan et al, 2010;Peng et al, 2013;Shi et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…This cell-type expression pattern extends to in vitro cell culture studies, which have also shown that the PRR is expressed in neurons but not astrocytes (Shan et al, 2010;Peng et al, 2013;Shi et al, 2014). Although these in vitro studies reported PRR expression in microglia, studies in mice provide no evidence for PRR localization in microglia in PVN tissue (Souza et al, 2019). On the other hand, a small number of microglia in human SFO tissue are reported to be positive for PRR immunoreactivity (Cooper et al, 2018).…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations